Evaluation of the residency training program of the Department of Pediatrics in the University of Perpetual Help Rizal Medical Center - Crisostomo, Virginia P.
The Residency Training Program of the Department of Pediatrics in the University of Perpetual Help Rizal Medical Center was established in 1983, initially accredited as Phase I by the Philippine Pediatric Society and later reaccredited as Phase II B. The School of Medicine was opened in 1996 and brought in medical students to the environment of the residency training program. Thru these changes the three-year residency program had produced forty-four graduates. Now on its twentieth year, a program evaluation of the residency training had not been done. This study was undertaken to evaluate the Residency Training Program of the Department of Pediatrics at the University of Perpetual Help Rizal Medical Center in terms of the following: quality and performance of the consultant?s, performance of residents-in-training, performance of graduates of the Residency Training Program, teaching-learning activities, availability of facilities and resources. It also aimed to determine the strengths and weakness of the program and to give suggestions on how to improve the program. As part of the evaluation process, questionnaires were sent which yielded a 75% response rate. Records were reviewed and the respondents (Consultants, Graduates, Residents) were interviewed. Data were analyzed qualitatively and quantitatively. Demographic data was analyzed using descriptive statistics. The distribution of the overall ratings of the respondents were compared using Wilcoxon rank sum test at 5% level of significance. Findings revealed that the Residency Training Program was properly implemented but needed improvements in some areas. The program had expert consultants but they were not always available. The residents were passing their evaluation but had to improve on their cognitive skills and attitudes. The graduates had good private practice but a significant number should be encouraged to take the Diplomate examination. The strong points of the training program were: expertise of the consultants, service rotations, and adequate teaching-learning activities. The weak points of the training program were the poor attendance of the consultants, inadequate clinical materials and facilities. Based on this study the following were proposed to improve the residency training program: (1) Provide independent study time and feedback of evaluation for the residents-in training (2) Encourage the graduates to take the Diplomate Examination by attending either a review class or the lectures in Pediatrics at the Jonelta School of Medicine and (3) for the administrators and consultants to address the weak points of the residency training program such as poor attendance to conferences, inadequate clinical materials and facilities.